2017
DOI: 10.1016/j.shaw.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Do Personality and Organizational Politics Predict Workplace Victimization? A Study among Ghanaian Employees

Abstract: BackgroundWorkplace victimization is considered a major social stressor with significant implications for the wellbeing of employees and organizations. The aim of this study was to examine the influences of employees' personality traits and organizational politics on workplace victimization among Ghanaian employees.MethodsUsing a cross-sectional design, data were collected from 631 employees selected from diverse occupations through convenience sampling. Data collection tools were standardized questionnaires t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In a cluster of participants of one study, people with Type A personality [48], less extroverted, less agreeable, less conscientious, less open to experience and more emotionally unstable were also more likely to be bullied [76]. Nevertheless, another study showed that personality characteristics explained only 2% of the variance (adjusted R 2 = 0.02) of bullying [58].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a cluster of participants of one study, people with Type A personality [48], less extroverted, less agreeable, less conscientious, less open to experience and more emotionally unstable were also more likely to be bullied [76]. Nevertheless, another study showed that personality characteristics explained only 2% of the variance (adjusted R 2 = 0.02) of bullying [58].…”
Section: Resultsmentioning
confidence: 99%
“…Effect sizes of the association between neuroticism and bullying were small, so residual confounding should be considered. The explanatory power of personality as a predictor of bullying was also very small [58]. One of the premises of occupational health actions is that the work environment and the work organization should be adequate to individual characteristics, not the opposite.…”
Section: Discussionmentioning
confidence: 99%
“…Results of Table 4 manifested that there is no relationship between agreeableness and POP ( β = −0.04, t = −1.126, p > 0.05). As the p -value of this relationship is not significant at 0.05 level of significance, it can be concluded that there is no effect of agreeableness on POP (Amponsah-Tawiah and Annor, 2017). Therefore, hypothesis 1c was rejected.…”
Section: Discussionmentioning
confidence: 81%
“…If an individual has an extrovert personality, then his/her POP will be less compared to its counterpart. In addition to this, results manifested that there is a significant and positive relationship between neuroticism and POP ( β = 0.247, t = 6.970, p < 0.01) (Amponsah-Tawiah and Annor, 2017). Therefore, hypothesis 1e was accepted.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation